Innovative Methods of Teaching Russian as a Foreign Language - Kalbayevna, Umarova Saniya (Journal of Sustainability in Integrated Policy and Practice, 2023)
In this article we analyzed innovative methods of teaching Russian as a foreign language. It is very important to study Russian, which is one of the leading languages of the world. All people of the world are not only witnessing to rapid changes in the multifaceted world, but are also direct participants in complex and continuous processes, such as the development and promotion of world culture, science and technology.